Antimicrobial Effects of Annona squamosa Leaf Extract on Staphylococcus aureus Growth: An In Vitro Study - Dwi Dianita Irawan; Amrina Nur Rohmah; Elia Ika Rahmawati; Risya Secha Primindari; Shinta Alifiana Rahmawati (Jurnal Bidan Cerdas, 2023)
Introduction: Mastitis is inflammation of the breast tissue due to infection with the Staphylococcus aureus bacteria causing local infections. It takes the natural ingredient Annona squamosal extract as an antimicrobial. Purpose: to determine the effectiveness of Annona squamosa leaf extract on the inhibition and killing power of Staphylococcus. Method: Experimental laboratory research with antibacterial activity test. Tube dilution method by incorporating bacteria and extracts with concentrations of 20%, 22.5%, 25%, 27.5%, 30%, and 32.5% and then measuring the MIC. The diffusion method is carried out by planting bacteria in a Nutrient Agar Plate and then giving the extract with 6 concentrations to calculate the MBC. Results: The results of the One-Way ANOVA test obtained a significance value of (p<0.001), indicating that changes in the concentration of Annona squamosa made a significant difference to Staphylococcus. The correlation test showed a significant p-value of (p<0.001), which means that there was a significant relationship between the administration of extract and the number of Staphylococcus. Conclusion: Annona squamosa leaf extract is able to significantly inhibit the growth of Staphylococcus bacteria and the higher the concentration of Annona squamosa leaf extract, the fewer the number of bacterial colonies that grow.